The mechanisms of generation of Unemployment in Iraq and its types and calculating the Disguised of it: Analytical Study for the period 2003-2015 - صالح, لورنس يحيى; نوري, محمد طاهر (Journal of Economics and Administrative Sciences, 2025)
The objective of this study is to attempt to provide a quantitative analysis to the causes of unemployment  in Iraq and its mechanisms of generation, as well as a review of the most important  types of both visible and invisible unemployment, and an attempt to measure the disguised  unemployment  and analyze the causes. The problem of the research lies in the fact that the Iraqi Economy has been suffered  for  a long time although its characterized by abundant  physical and natural  resources, from the existence of the  phenomenon of unemployment  in the previous two types. Causing a lot of economic problems, represented by the great waste of resources and the lack of utilization of human potential available in the operation and production, as well as the social problems of low level of Income and poverty. Hence the importance of research is an attempt to study and analyze the most important manifestations of this phenomenon by returning to its real causes, using quantitative and relative related indicators. The study concluded that the problem of unemployment in Iraq is result of the interaction of all Structural Imbalances experienced by the economy, especially the Imbalances of production structure and the consequent deficiencies in the sectors which absorb labor, this was due to the Imbalance  of the structure of foreign trade represented by the unfavorable tendency towards imports, which led to almost complete cessation of production and the decline of non-oil exports. This has caused an Imbalance in the labor market, that has become in the disproportionate between the supply  and demand of labor, all these reasons has contributed to widespread unemployment. The researcher recommends that the best solution to overcome the problem lies by taking many actions, the most important of which is to support and diversify sectoral production growth to ensure optimal utilization of resources, because this will absorb the labor  forces, moreover it can be minimize the causes of unemployment by harmonization the outputs of the educational system with needs of labor market, as well as by training cadres and increasing their qualifications in proportion to the nature of the available jobs. As for the disguised unemployment can be reduced by making government employment conditional on its actual urgency, on the other hand, it is possible to develop employee methods of existing government employees and transform them into productive workers, by creating investment opportunities in partnership with the private sector, and review the plans of manage and exploit the government  resources in optimally, and fighting financial and administrative corruption.